Seleção de famílias de feijoeiro baseada na produtividade e tipo de grãos e informações de QTLs - Torga, Paula Pereira (2008)
Nowadays the carioca type common bean is the most used in Brazil. The selection of superior families mainly on grain yield and grain type is very important for achieving success in the breeding program. The objectives of this research were selecting families with high grain yield based on yield itself and on molecular markers linked to the yield QTLs, and also families with better grain type. One hundred F3:7 families were evaluated in three seasons, in two field experiments per season. Two experiments were set up in Lavras and Ijaci county in the dry season/2007, other four experiments were set up in Lavras and Lambari, two in the winter season/2007 and two in the rainy season 2007/2008. A 10x10 lattice design was used in all experiments, using 2m-long plots and rows 50cm apart. The families were evaluated based on grain yield in all experiments, and based on grain type in one experiment per season. Also, 480 microsattelite markers were tested in the parents. Eight markers were polymorphic and used for genotyping the families. Among them five explained part of the grain yield variability and presented high interaction by environments. Only one marker showed to be more stable and was used in the selection assuring a genetic gain of 0.16%, much smaller than the phenotypic gain of 7.43% on grain yield and 9.58% on grain type. The phenotypic selection intensity was 5%.